2010
DOI: 10.1007/s00423-010-0697-z
|View full text |Cite
|
Sign up to set email alerts
|

Results of adrenal surgery. Data of a Spanish National Survey

Abstract: In Spain, adrenalectomy is performed in hospitals of varying complexity. Laparoscopic approach is the rule, with good results in terms of morbidity and stay. High-volume centers and surgeons had best results in terms of use of minimally invasive surgery and hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 17 publications
2
12
0
1
Order By: Relevance
“…This is a significant consideration given the results of a recent cohort analysis of 3,144 adrenalec- tomies performed where the surgeon volume was found to be an independent predictor of postoperative complications [17]. These results were further confirmed in a Spanish national survey where surgeons and center volume were found to be major factors in the outcome of adrenal surgery [18].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is a significant consideration given the results of a recent cohort analysis of 3,144 adrenalec- tomies performed where the surgeon volume was found to be an independent predictor of postoperative complications [17]. These results were further confirmed in a Spanish national survey where surgeons and center volume were found to be major factors in the outcome of adrenal surgery [18].…”
Section: Discussionsupporting
confidence: 75%
“…An improved survival rate was also reported for a large series of ACC patients treated at a single tertiary care referral center where patients underwent surgeries that achieved a complete resection of all gross disease [12]. Additional studies have also clearly demonstrated that increased surgeon and hospital volume are positively associated with improved patient outcomes following adrenalectomy [17,18]. As a consequence, we can argue a similar advantage in terms of oncologic outcome, including improved disease-free survival (DFS) and overall survival (OS) rates, for ACC patients who receive early specialized care at high-volume centers (HVC).…”
mentioning
confidence: 83%
“…2–5 Previous studies have demonstrated that increased surgical volume is an independent predictor of lower rates of postoperative complications and shorter length of stay for patients undergoing adrenalectomy in the United States and Spain. 18,19 Furthermore, greater surgical experience has been associated with improved oncologic outcomes for patients with ACC. For example, Kerkhofs et al evaluated patients with stage I to III ACC followed in the National Cancer Registry in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Specialization of surgical treatment in rare conditions has been a controversial issue for many years, but increasing evidence suggests that treatment outcome is improved by centralization of care in specialized, high-volume centers (9,10,11,12). There is supporting evidence that this is also the case for adrenal surgery (13,14).…”
Section: Introductionmentioning
confidence: 92%